The ride of the parasite: a 100-million-year old mantis lacewing larva captured while mounting its spider host - Joachim T. Haug; Patrick Müller; Carolin Haug (Zoological Letters, 2018)
Abstract Background Adult mantis lacewings, neuropteran holometabolan insects of the group Mantispidae, possess anterior walking legs transformed into prey-catching grasping appendages reminiscent of those of praying mantises. While adult mantis lacewings are hence active “wait-and-catch” predators, the larvae of many mantis lacewings have a quite different biology: first-stage larvae seek out female spiders, mount them, and either wait until the spider has produced an egg sac or, in some cases, choose a female already bearing an egg sac. The larva then enters the egg sac and feeds on the eggs. While first stage larvae are highly mobile with comparably long legs and a certain degree of dorso-ventral flattening (“campodeiform”), larval stages two and three are almost immobile, grub-like, and simply remain within the egg sac. Fossils of mantis lacewings are relatively rare, fossils of larval mantis lacewings are even rarer; only a single larva sitting on a juvenile spider has been described from ca. 50 million year old Baltic amber. Results Here we describe a second occurrence of a larval mantis lacewing from significantly older Burmese amber, about 100 million years old. The specimen is preserved in a position right at the leg of a spider, similar to modern-day larvae that are about to mount their prospective host. The claws of the larva can be seen to grab around the leg of the spider. Conclusions We discuss how reliable these fossils are as indicators of palaeo-parasitism, and in which aspects the behaviour of mantis lacewing larvae in general indeed represents parasitism. While the specimen appears to be about to board the spider, it may not necessarily represent a parasite in the strict sense. Evaluating the actual ecological role of a fossil heavily depends on comparison to modern forms, and not all modern-day larvae of Mantispidae are parasites. We therefore provide a closer look into the known feeding habits of modern mantis lacewing larvae.